Collective action and marketing of underutilized plant species: The case of minor millets in Kolli Hills, Tamil Nadu, India - Gruère, Guillaume P.; Nagarajan, Latha; King, E. D. I. Oliver (International Food Policy Research Institute, 2007)
Minor millets are examples of underutilized plant species, being locally important but rarely traded internationally with an unexploited economic potential. In the Kolli hills of Tamil Nadu, India, a genetically diverse pool of minor millet varieties are grown by the tribal farming communities to meet their subsistence food needs. Most of these minor crops were not traded outside the farming community. Despite a consumption preference among the farming communities for minor millets, in the recent past the acreage under minor millet crops have declined considerably due to the availability of substitute cash crops. As a response, the M.S. Swaminathan Research Foundation (MSSRF) based in Chennai has led targeted conservation cum commercialization intervention programs over the last 7-9 years in the Kolli Hills. In this paper we provide a first evaluation of the success of marketing development for minor millets in the Kolli Hills with a specific focus on collective action and group initiatives undertaken by the women and men self-help groups organized by the concerned non-governmental organization. We analyze the key collective actions that are taking place in the minor millet marketing chain through a series of field visits and focus group discussions with the stakeholders involved. We then compare the role of collective action in this new market with the case of marketing chains for cassava and organic pineapples, two cash crops with an expanding production in Kolli Hills. Our analysis shows the critical role of collective action and group initiative as a necessary but not sufficient condition for the successful commercialization of underutilized plant species for the benefit of the poor and the conservation of agrobiodiversity.